The human soul, free will and determinism under capitalism through Cronenberg’s films - Yamalıoğlu, Beste. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
In this thesis, I will explore the effects of capitalism on human nature, in particular on whether we have free will or not, as portrayed in David Cronenberg films. In the first half I will make an introduction to determinism and relate the debate between compatibilism and incompatibilism. Then I will deal with the question of whether there is a human nature, and if there is whether it is fixed or not, historical or ahistorical, based on a basic comparison of Sartre, Marx and Freud on this issue. I will give Sartre’s defense of free will and Marx’s historical account of human nature. In the second half, I will describe Freud’s deterministic human nature concept and analyze Cronenberg’s main characters who think they have free will while they are living in fully determined worlds regarding these issues. Are they in self-deception (if incompatibilism is right) or not (if compatibilism is right)? Using Marcuse’s arguments I will argue that they are in self- deception and this is a feature of how capitalism shapes individual psychodynamics. At the end of the thesis I will explore Marcuse's optimism about the future as based on compatibilism compared with Cronenberg's pessimism that is based on his incompatibilist ideas. I will try to see whether an alternative society is possible in which technology is used as a means for emancipation. Here I will compare and relate Marcuse’s, Haraway’s and Wilde’s arguments on the emancipator potentials of technology.